Les formations sociales et les processus de leur délitement - Romain Huët; François Cooren (Communication)
The authors propose to analyze a specific period of time where people stumble and get stuck to the point that the organizational form that they founded and partly institutionalized does not seem strong enough to hold them together. This article aims to focus on the organizational dynamics, their fragility and their possible disintegration. It takes an empirical case study to show how a particular social formation emerged, configured itself and was ultimately dismantled. In particular, the authors show how actors attempt to stabilize their initiative by formatting and structuring it and what kind of practical difficulties they face in doing that.